2019
DOI: 10.2147/cmar.s211119
|View full text |Cite
|
Sign up to set email alerts
|

<p>Spatial heterogeneity of <em>KRAS </em>mutations in colorectal cancers in northern France</p>

Abstract: BackgroundSomatic mutations in the KRAS gene are the most common oncogenic mutations found in human cancers. However, no clinical features have been linked to KRAS mutations in colorectal cancer [CRC].PurposeIn this study, we attempted to identify the potential geographical population clusters of KRAS mutations in CRC patients in northern France.Patients and methodsAll patients with CRC who were identified to have KRAS mutations between 2008 and 2014 at the Regional Molecular Biology Platform at Lille Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…The frequency of KRAS mutations (exon 2 and exon 3) in our cohort reached 61.88%. This was much higher than what was reported in the Asia-Pacific (37-52%) and Western populations (32-49%) [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Nevertheless, our data is in line with a previous study in Indonesia, showing that KRAS mutation was found in 71.8% of serrated adenocarcinoma (SA), which is intriguingly higher than the generally reported incidence of 40% [39][40][41].…”
Section: Discussionsupporting
confidence: 82%
“…The frequency of KRAS mutations (exon 2 and exon 3) in our cohort reached 61.88%. This was much higher than what was reported in the Asia-Pacific (37-52%) and Western populations (32-49%) [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Nevertheless, our data is in line with a previous study in Indonesia, showing that KRAS mutation was found in 71.8% of serrated adenocarcinoma (SA), which is intriguingly higher than the generally reported incidence of 40% [39][40][41].…”
Section: Discussionsupporting
confidence: 82%
“…25,26 Still, to date, there are only sparse data on geographic variability of CRC mutations. Turpin et al 27 evaluated patients with CRC from northern France and showed spatial heterogeneity that might correlate with environmental factors, such as proximity to major highways and large cities. The association of KRAS mutation with African American race, female sex, and West South Central US state residence further raises the question of whether the geographic differences of KRAS status are affected by racial distribution differences.…”
Section: Discussionmentioning
confidence: 99%